Commentary: After the flush: What is the best fecal waste management system for Addis Ababa?. (June 2022) - Nieguitsila, Adelaïde
Highlights: Management of faecal waste. diversity of system in this case. Involvement of local authorities. Possibility of using this waste management system in education.